IMPLEMENTASI KABIJAKAN PEMBANGUNAN INFRASTRUKTUR JALAN DALAM MENDUKUNG PENGEMBANGAN EKONOMI MASYARAKAT DI KABUPATEN SORONG PROPINSI PAPUA BARAT - SAHUDEGE, CHRISTIN DESSY; Kiyai, Burhanuddin; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2015)
Implementation of Road Infrastructure Development Policy in Support of Community EconomicDevelopment in Sorong. This study aims to find out about the Road Infrastructure Development inSupport of Economic Development conducted by the government of Sorong in particular Umum.OlehWorks Department for the government's role in encouraging the development area should be donewith a set of policies and actions that can improve regional economy Sorong.This study was conducted in Sorong, the process of data collection is done by observation, interviewand documentation. Informants in this study consisted of 14 people. The data collected later describedby using qualitative methods.Results from this study indicate that the construction of road infrastructure in Sorong Regency is goodenough, but not fully wishes of the people can be responded to by the government, especially theDepartment of Public Works. Thus the author can propose to the government to the natural resourcesthat could be used for the benefit of local communities in Sorong for the present and the future.Keywords: Implementation, Policy, Infrastructure Roads and Economic Development